Money as a computational machine - Inigo Wilkins; Bogdan Dragos (Finance and Society, 2022)
This article presents a speculative philosophical account of money as a computational machine. It does so by leveraging a computational and machinic framework, drawing primarily from the work of Philip Mirowski and Jean Cartelier. The argument is focused on a specific level of abstraction, i.e., the monetary operations involved in the creation and transfer of units of account, asking whether it is possible to view these operations as computations that mediate economic relations. As the primary function of such a machine would be one of social coordination, the article also highlights the political consequences of its implementation across society.
Keywords: 300; Money; computation; machine; hierarchy; Mirowski; Cartelier